Aortic body paraganglioma in dog - Leal Bertolo, Paulo Henrique [UNESP]; Miranda de Aguirra, Lucien Roberta Valente; da Gama Barbosa Monger, Suellen; de Castro Cardoso, Adriana Maciel; de Oliveira Vasconcelos, Rosemeri [UNESP]; Assunção Pereira, Washington Luiz (My University, 2017)
Background: Aortic body paragangliomas are uncommon neoplasms that develop mainly in aortic and carotid bodies. It has been supposed that genetic factors and chronic hypoxia may stimulate tumor development. The brachycephalic dog breeds, as Boxer, are most predisposed to present this neoplasm. The clinical symptomatology is related to tumor size and localization. Usually aortic body paraganglioma has benign biological behavior, when it is malignant, rarely promotes metastases. The aim of this study was to report a case of the aortic body paraganglioma as death cause in a dog. Case: A canine, 10-year-old, male, cross breed, presented clinical signs as anorexia, emesis, cough, dyspnea and exercise intolerance. After death the animal was examined at the Department of Veterinary Pathology at the Federal Rural University of Amazonia. On necropsy, no pericardial effusion was identified, however pleural and abdominal effusion was observed, volume like 1000 and 700 mL, respectively. The heart had a neoplasm near the left atrium, it measured 6.5 x 8.2 cm, had irregular surface, firm consistency, grayish color, and at the cut showed infiltration in the myocardium, as well as obstruction of the left atrial lumen and left ventricle concentric hypertrophy. No distant metastases were found. Microscopically, the tumor consisted of polyhedral morphology cells, eosinophilic cytoplasm, spherical and hyperchromatic nucleus. Cells were grouped into lobes separated by fibrovascular stroma, large cells (less uniform cells), low mitotic rate and myocardial infiltration. On immunohistochemical analysis anti-cytokeratin, anti-vimentin and anti-S-100 antibodies were used. Tumour cells stained was absent for anti-cytokeratin and anti-vimentin, but was anti-S-100 positive. A case of malignant aortic body paraganglioma grade II was diagnosed. Discussion: The reported case was diagnosed in cross breed dog. However, brachycephalic dog breeds, as Boxer, are more predisposed to develop this kind of tumor. The development of these tumors is related to the genetic factors and chronic hypoxia. It was suggested that the tumor origin on this case is related to genetic factors, because the animal had no respiratory diseases, he was not brachycephalic and lived in a low altitude city, what exclude the possibility to have been induced by chronic hypoxia imposed by low oxygen. The clinical symptomatology presented by the animal days before death was related to the localization and size of the tumor. The macroscopic findings were similar to those of other studies. And the histopathological findings of the report were indicative for the histological classification of malignant aortic body paraganglioma. On immunohistochemical analysis it was negative for anti-cytokeratin and anti-vimentin antibodies, however was positive for anti-S-100 antibody, thus differentiated from other tumors that may occur in this local and confirmed the diagnosis of malignant aortic body paraganglioma grade II. The dog died due to tumor-related causes, however some authors indicate de tumor as a necropsy finding. The findings made it possible to conclude that tumor was aortic body paraganglioma and that it promoted cardiorespiratory complications related to localization and infiltration, what was worsened by pleural effusion leading the animal to the cardiogenic shock that culminated with death. It shows the importance of including this tumor in the list of differential diagnoses of heart diseases in dogs.
Paraganglioma de corpo aórtico em cão
Keywords: Canine; Cardiac neoplasm; Chemodectoma; Veterinary cardiology; Veterinary oncology